A rapid approach for informing the prioritization of degraded agricultural lands for ecological recovery: A case study for Colombia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
A first study case was successfully developed in Colombia prioritizing over 10 million hectares of degraded land for ecological restoration. This approach can be scaled up over Latin America and the Caribbean leveraging on the CCAFS-led LAMNET and LCL-RN networks.